Engineering and ergonomics—an important aspect in fruit harvesting systems - Suhail Nazir Wani; Sanjay Mohan; Mohd. Kamal Mohd. Shah (Springer, Singapore, 2022)
Fruits are an integral part of all civilizations, and harvesting of them has always been a challenge. Fruits are subjected to damage while harvesting and personals involved also are subjected to various health issues. Growing of fruits has been a major component in most of the countries which even adds to the GDP of the nation. Scientists and researchers from various streams have been exploring the possibilities to enhance the growth and harvesting of fruits. Engineers and ergonomists, nowadays, are developing various alternative systems to safeguard the fruit and the persons involved in harvesting as this is influencing the productivity to a larger extent. This paper brings forth the past and recent happenings in the fruit harvesting systems, especially apple harvesting systems. The paper also focuses upon the shortcomings in the existing apple harvesting systems which are affecting the fruit harvesting setup as a whole. With this article, authors have tried to throw light on the existing harvesting systems and various possibilities to bring innovation in the existing systems.